Near Sea-Surface Mobile Radiowave Propagation at 5 GHz: Measurements and Modeling - Lee, Yee Hui; Dong, Feng; Meng, Yu Song (Společnost pro radioelektronické inženýrství, 2014)
Near sea-surface line-of-sight (LoS) radiowave propagation at 5 GHz was investigated through narrowband measurements in this paper. Results of the received signal strength with a transmission distance of up to 10 km were examined against free space loss model and 2-ray path loss model. The experimental results have good agreements with the predicted values using the 2-ray model. However, the prediction ability of 2-ray model becomes poor when the propagation distance increases. Our results and analysis show that an evaporation duct layer exists and therefore, a 3-ray path loss model, taking into consideration both the reflection from sea surface and the refraction caused by evaporation duct could predict well the trend of LoS signal strength variations at relatively large propagation distances in a tropical maritime environment.
Keywords: Channel modeling; evaporation duct; maritime mobile; path loss prediction; sea reflection